STUDYING SWELLING SOILS BY MULTIDIMENSIONAL STATISTICAL ANALYSIS METHODS AS THE BASIS FOR ENGINEERING STRUCTURES FOUNDATIONS IN SUDAN - Chomko, D.; Chomko, F.; Cherkashyna, N.; Taranov, V.; Seifeldin, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new way to study swollen soils as the basis for foundations by methods of mathematical statistics, including cluster, factor and correlation-regression analyses has been proposed in the article. Normative values of the strength characteristics of these soils depending on their physical properties and degree of swelling, application limits, predominant factors and correlations between different indicators of soil properties have been established according to the results of these analyzes. A method of the study area zoning, leading to possible differential application of soils normative characteristics, as well as proposals for designing foundations on swollen soils have been developed. The methods were tested on the soils of Sudan.
Keywords: swelling soils; physical properties; degree of swelling; bearing capacity; zoning of the territory; foundations; cluster; factor and correlation-regression analyzes; predominant factors and correlation dependencies